(untitled) (diségno, 2024)
Once he assumed the Spanish throne after his reign in Naples, Charles III began an ambitious project for the elaboration of a set of models of the most important strongholds in Spain, in order to facilitate the comprehensive understanding of these cities and as a means to make proposals for improvement, mainly in their fortifications. The first project was developed in the city of Cadiz –the main commercial port of the Indies and strategic enclave of the country– between 1777 and 1779, under the direction of Francesco Sabatini, Royal architect, who appointed Alfonso Ximénez, military and model maker, to execute it in the city together with a large multidisciplinary team. As a result, they made a model larger than 100 m² of surface at ±1:250 scale, using noble materials, such as different types of wood, ivory, and silver, constituting an exception among the urban models that had been made so far, both for its size and richness, as well as for its level of abstraction. In this article we will approach this singular and unique exercise by contextualizing it in the European panorama of the time, as well as through its analysis and three-dimensional survey, which will offer new perspectives and will allow us to contrast its accuracy and relationship with historical cartographies, in order to finally value and vindicate the exceptional nature of this graphic contribution in the form of a model.